2017
DOI: 10.1007/s11136-016-1493-1
|View full text |Cite
|
Sign up to set email alerts
|

How different cystoscopy methods influence patient sexual satisfaction, anxiety, and depression levels: a randomized prospective trial

Abstract: PurposeBladder cancer (BC) is one of the most common cancers worldwide. BC diagnosis and surveillance is based on cystoscopy (CS). CS impact on patient’s depression, anxiety, and sexual satisfaction (SS) is not sufficiently studied. There are no data on patient’s comfort with flexible or rigid CS.MethodsWe prospectively evaluated pain perception (PP), depression, anxiety, and SS of 100 male patients who previously underwent at least one rigid CS in our department as surveillance after TURB procedure due to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
2
25
0
1
Order By: Relevance
“…Sexual problems are known to have a significant impact on QoL which makes this development in Fig. 2 a paramount finding in this review [41].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual problems are known to have a significant impact on QoL which makes this development in Fig. 2 a paramount finding in this review [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previously cystoscopy related pain was evaluated with 10-point visual analog self-assessment scale and reported to be ranging from 2.5 to 4.5 points for flexible and 2.8 to 5.1 points for rigid instrument use (4-7). Krajewski et al showed the superiority of flexible CS over the rigid one in terms of pain perception, but also in sexual satisfaction or anxiety levels in male patients who were under cyclic surveillance because of NMIBC (8). We have demonstrated significant reduction of pain in the FC arm (2.57±1.83 vs. 4.48±2.18, p<0.01).…”
Section: Resultsmentioning
confidence: 49%
“…No significant change in sexual function was found at the fourth week compared with that at the preoperative baseline. Patients were reported to have had a more comfortable experience after flexible ureteroscopy with decreased pain and anxiety [25]. Nevertheless, in general, sexual dysfunction rarely occurs, even after rigid endoscopy.…”
Section: Discussionmentioning
confidence: 99%